Enhanced CO2 outgassing in the Southern Ocean from a positive phase of the Southern Annular Mode - Lovenduski, Nicole S.; Gruber, Nicolas; Doney, Scott C.; Lima, Ivan D. (Global Biogeochemical Cycles, 2007)
ISSN:0886-6236 ISSN:1944-9224